Types and Abundance of Peripyhton in the Pipe Placed in The Air Hitam River, Pekanbaru City, Riau Province - Naziruddin Naziruddin; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractPeriphyton is a sessile microscopic organism that attach on certain substrate. Research aims to determine the type and abundance of periphyton on Pipe substrate has been carried out in April-May 2018 in the Air Hitam River. There were three sampling stations, namely S1 (in the upstream), S2 (in the middle) and S3 (in the downstream). Samplings were conducted once/week for a 3 weeks period. The periphyton samples are brushed from the pipe substrates (8 x 6) cm2. The number of substrates in S1, S2 and S3 were 5, 4, and 3 pieces respectively. Water quality parameter measured were water current, temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. Results shown that there were 35 types of periphyton present and they were belonged 5 classes, namely Bacillariophyceae (17 species), Cyanophyceae (4 species), Chlorophyceae (10species), Euglenaphyceae (3 species) and Xantophyceae (1 species) . The abundance of periphyton in the pipe substrate in the S1 was 35,609 cells/cm2, in S2 was 66,989 cells/cm2and in S3 there was 140,470 cells/cm2. The water quality parameters were as follows: water current 0.08-0.46 m/s, transparency:18-29 cm, temperature 29-29,30C, dissolved oxygen 3.43-3.56 mg/L, free carbon dioxide1 6,2-7,9 mg/L, nitrate 0.302-0.529 mg/L, phosphate 0.348-0.542 mg/L. Keywords: lotic, sessileorganism, water quality,plastic substrats